If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2s + -3) + -9 = -2(7s + 7) + -2 Reorder the terms: -3(-3 + 2s) + -9 = -2(7s + 7) + -2 (-3 * -3 + 2s * -3) + -9 = -2(7s + 7) + -2 (9 + -6s) + -9 = -2(7s + 7) + -2 Reorder the terms: 9 + -9 + -6s = -2(7s + 7) + -2 Combine like terms: 9 + -9 = 0 0 + -6s = -2(7s + 7) + -2 -6s = -2(7s + 7) + -2 Reorder the terms: -6s = -2(7 + 7s) + -2 -6s = (7 * -2 + 7s * -2) + -2 -6s = (-14 + -14s) + -2 Reorder the terms: -6s = -14 + -2 + -14s Combine like terms: -14 + -2 = -16 -6s = -16 + -14s Solving -6s = -16 + -14s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14s' to each side of the equation. -6s + 14s = -16 + -14s + 14s Combine like terms: -6s + 14s = 8s 8s = -16 + -14s + 14s Combine like terms: -14s + 14s = 0 8s = -16 + 0 8s = -16 Divide each side by '8'. s = -2 Simplifying s = -2
| x*y=1512 | | 10x-4x= | | 6timesx=4 | | 5(x-7)=40 | | 5z-10z=45 | | y=-3/5x+b | | -1xy+2x^2+-6y^2= | | 6x^2-3xy-18y^2= | | (2/x-7)=3 | | (11b-4)-5(2b+1)=-5 | | 2x^7+2x^6-4x^5= | | (9x-9/7)+(8-x/3)=9 | | 9x+5x+3+8=11x+4+2x | | 33*w=52 | | (6x^2+22+17)/(x+3) | | w*2w-5=52 | | 2w^2-5w-17-w^2+2w-1=0 | | 2w^2-5w-17-w^2+2w-1=00 | | 2u^2-24u+70-u^2+14u-49=0 | | 2w^2-3w-16-w^2+4w-4=0 | | 2x^2-8x-8-x^2+4x-4=0 | | (x+2)/(x-6)=55 | | 2v^2+v+30-v^2+8v-16=0 | | 2y^2-3y+5-y^2+6y-9=0 | | 2m-4+12=3m-4+2 | | 2y^2-3y+5-y^2-6y+9=0 | | 2y^2-3y+5+y^2-6y+9=0 | | 24x^2-49x-40=0 | | 2m-4+12=2m-4+12 | | -12x^2+45x+12=0 | | 2y^2-y-29-y^2+2y-1=0 | | 2v^2+9v+10-v^2-4v-4=0 |